Foreign language learning boredom and enjoyment: The effects of learner variables and teacher variables - Li, Chengchen (Language teaching research : LTR, 2025)
The past decade has witnessed a surge of research interest in diverse emotions that foreign/second language (L2) learners experience. However, research on L2 boredom is just starting. The current study focuses on foreign language learning boredom (FLLB) and foreign language enjoyment (FLE), and examines how they are associated with a wide range of learner-internal variables and teacher-centered variables. A total of 868 current university students in China studying English as a foreign language (FL) participated in a questionnaire survey. Correlation results show the following: (1) there was a strong negative correlation between FLE and FLLB; (2) FLE was positively linked to multiple learner-internal variables (self-perceived FL proficiency, relative standing among peers, attitudes towards the FL, the teacher, and FL-related culture) and teacher-related variables (the use of FL in class, enthusiasm, predictability, and friendliness), while negatively linked to learner age and onset age of FL learning; (3) these significant correlates of FLE were linked to FLLB in an opposite way. When the significant variables were entered into the regression models, attitudes toward the FL stood out as the strongest learner-internal predictor of both FLE and FLLB, while teacher friendliness was shown to be the strongest teacher-related predictor of both emotions. The findings show that FL emotions are contingent on the interplay between learners and teachers. In accordance with the findings, I recommend that enjoyment-boosting and boredom-reducing activities be incorporated into FL classrooms.